ARTISTIC IMAGE AS A FACTOR OF COGNITION OF REALITY (ON THE EXAMPLE OF THE STORIES OF ISAJAN SULTAN) (Scientific journal of the Fergana State University, 2024)
It is known that in the literary work, artistic images are perceived as objects with real empirical feelings. Writers express the image of the world and people in their works. It should be said that an artistic image not only shows the proper image of nature, animal world, man, and interpersonal relations in general. If the artistic work is the main unit of literature, then the artistic image is the main unit of literary creation. An image object is developed with the help of artistic images. Landscape and interior subjects, events and actions of heroes are expressed through the image. In this article, the interpretation of the artistic image as a factor of expression of existence is revealed on the example of the stories of the famous writer Isajon Sultan.